Tracheobronchial remnant as a cause of oesophageal stricture in children – case report and review of the literature - Szymczak, Marek; Trypens, Agata; Kowalewski, Grzegorz; Polnik, Dariusz; Broniszczak, Dorota; Łyszkowska, Małgorzata; Majak, Dorota; Woynarowski, Marek; Pronicki, Maciej; Kaliciński, Piotr (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Tracheobronchial remnant (TBR), one of the causes of congenital oesophageal stenosis (COS), is a rare anomaly, the treatment of which is hampered by the lack of well-established therapeutic strategies. A definite diagnosis of TBR can be made only by histopathological examination of the resected segment. A 10-month-old girl was admitted to a district hospital due to dysphagia, intolerance of solid food, and regurgitation. The patient was referred to our hospital for continuation of the treatment. She underwent a laparotomy, segmental resection of the oesophageal narrowing, end-to-end anastomosis, and anterior fundoplication. Surgical excision of the stricture is the only effective treatment of a patient with TBR.